Precocious puberty as a consequence of anti-NMDA receptor encephalitis in children - Po-Ming Wu; Chao-Ku Teng; Yen-Yin Chou; Yi-Fang Tu (Elsevier, 2021)
Background: Anti-N-methyl-D-aspartate (NMDA) receptor encephalitis is one of the most common autoimmune encephalitis in children. Most children recovered well after anti-NMDA receptor encephalitis. However, the NMDA receptor network functions are critical for the developing brain in children. The long-term consequences in pediatric patients of anti-NMDA receptor encephalitis are very infrequently reported. Methods: This case series study retrospectively enrolled 10 children aged below 18 years old with antibody-proved anti-NMDA receptor encephalitis in a tertiary medical center from 2010 to 2019. Long-term neurological consequences of anti-NMDA receptor encephalitis in children were followed. Results: One boy and nine girls were enrolled with a median onset age of 3.6 years. The most common initial presentation was verbal reduction and psychiatric symptoms soon after some flu-like prodromal symptoms. Nearly all patients then developed decreased level of consciousness, mutism, seizures and orofacial-lingual dyskinesia. Autonomic instability occurred in 5 patients, particularly in pre-pubertal children. Only one adolescent patient had ovarian teratoma. All patients survived after immunotherapy and were followed for 5.8 ± 3.3 years after discharge. Four had epilepsy within 2 years after encephalitis, four had a cognitive deficit, one had mild psychiatric symptoms of hallucination, and none had residual involuntary movements. Moreover, two pre-pubertal children developed central precocious puberty about 3 years after encephalitis, and one required gonadotropin-releasing hormone agonist treatment. Conclusion: Central precocious puberty could be a consequence of anti-NMDA receptor encephalitis in the pre-pubertal children. The pediatrician should pay attention to its occurrence at follow-up.